2018
DOI: 10.3892/or.2018.6847
|View full text |Cite
|
Sign up to set email alerts
|

Fascin is involved in cancer cell invasion and is regulated by stromal factors

Abstract: The tumor microenvironment plays an important role in cancer growth, invasion and metastasis. The stroma surrounding a tumor is known to contain a variety of factors that can increase angiogenesis, cancer growth and tumor progression. The aim of the present study was to determine the role of fascin in cancer growth and invasion and identify stromal factors involved in cancer progression. A fascin-depleted cell line (fascin dep ) was used to observe the role of fascin in cancer invasion. Compared with wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…1, recombinant IL-1β treatment incresed invasion 2.75-fold compared to the control. To investigate the expression of IL-1β in the tumor, we used a xenofrafted tongue tumor specimen established in our previous experiments (8). IL-1β expression was located in the cytoplasm of the cancer cells and cancer-associate fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, recombinant IL-1β treatment incresed invasion 2.75-fold compared to the control. To investigate the expression of IL-1β in the tumor, we used a xenofrafted tongue tumor specimen established in our previous experiments (8). IL-1β expression was located in the cytoplasm of the cancer cells and cancer-associate fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…The xenograft tumor tissue was used to observe the expression of IL-1β. Tumor xenograft was established by implatation of OSCC cells in athymic nude mouse in our previous study (8). Briefly, OSCC cells were injected into mouse tongue and growth of tumor xenografts was observed for 5 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…139 Signal transducer and activator of transcription 3 (STAT3) and nuclear factor kB (NF-kB) are two well-known TFs required for the cytokine-induced expression of FSCN1 in human cancer cells. [140][141][142][143][144] FSCN1 expression is induced by a variety of cytokines, such as IL-6, tumor necrosis factor (TNF)-a, and oncostatin M (OSM). These cytokines activate STAT3 and NF-kB in human breast and gastric cancer cells to induce the expression.…”
Section: Fscn1 Upregulation Mechanisms In Cancermentioning
confidence: 99%
“…It is believed that fascin overexpression is a subject to an inflammation-mediated regulation. It has been reported that inflammation-related cytokines such as tumor necrosis factoralpha (TNF-α), IL-1β and transforming growth factor-beta (TGF-β) may upregulate fascin [27,28]. Thus, it can be assumed that E407a-induced tissue damage and destruction resulted in the development of inflammation and subsequent overexpression of fascin in the most damaged areas due to the pro-inflammatory microenvironment.…”
Section: Discussionmentioning
confidence: 99%